Shifting Strategy and Actor on Indonesia’s Hajj Diplomacy in the era of Pandemic Covid-19 - Herningtyas, Ratih (Technium Social Sciences Journal, 2025)
Indonesia as a Muslim-majority country, the implementation of the Hajj pilgrimage is one of the policy priorities and state obligations that must be fulfilled. The limited quota of pilgrims provided by the Government of Saudi Arabia to be able to perform the Hajj pilgrimage each year causes the Indonesian government to carry out intense Hajj diplomacy. Indonesia’s Hajj Diplomacy has been carried out toward the Government of Saudi Arabia, especially to obtain additional quotas and adequate Hajj services. However, the Covid-19 pandemic has caused the Government of Saudi Arabia to establish additional vaccine regulations, reduce the quota of pilgrims and even close its territory for the implementation of hajj for foreign citizens from abroad in 2020 and 2021. This has led to an increasingly long waiting period for Indonesian Muslims to be able to conduct the hajj pilgrimage. Using the concept of diplomacy, this paper finds that the Indonesian government has changed strategies and actors in the implementation of its hajj diplomacy during the pandemic. Indonesia’s Hajj diplomacy during the pandemic is focused on negotiating vaccine requirements and involving non state actor.